Awareness and Willingness to Vaccinate against COVID-19 among Pregnant Women and Reasons Influencing their Decision in Poland – a Survey-Based Study - Baran, Milena; Kuleta, Martyna; Staniszewska, Izabela; Mączyńska, Wiktoria; Pater, Mikołaj; Kazimierska , Karolina (Journal of Education, Health and Sport, 2024)
Introduction: The COVID-19 pandemic has lasted for over 2 years and has resulted in more than 486 million cases and over 6 million deaths worldwide. Pregnant women are a special group of society exposed to severe or unpredictable course of infection. Purpose of work: Assessment of awareness and willingness to vaccinate pregnant women against COVID-19 and reasons influencing this decision. Materials and methods: The proprietary online survey addressed to women in Poland during pregnancy and women who were pregnant in the period from December 27, 2020 (introduction of the vaccine in Poland) to 20.03.2022. The study included a total of 518 respondents of reproductive age, among which 398 have a university degree and 108 have secondary education. 376 respondents got vaccinated against COVID-19 — 120 before getting pregnant, 199 during pregnancy and 57 after giving birth. Summary: Most of the surveyed women (321) hadn’t had a positive PCR test for COVID-19 until the day of the survey, but 38% had a positive PCR test. Asked about reasons for getting vaccinated during pregnancy, most of the respondents stated that people should get vaccinated against COVID-19 in general, they got vaccinated because of the baby’s health, and that they acted according to the recommendations of The Polish Society of Gynecologists and Obstetricians and the World’s Health Organization. On the other hand, most of the women didn’t get vaccinated because they were afraid of the side effects, there is not enough research on the topic, and they believe that the vaccination is ineffective. Additionally, 154 respondents were encouraged by the doctors to get vaccinated in opposite to 21 who were discouraged by the doctor. The majority of the respondents are aware of the great risk of COVID-19 infection during pregnancy. Therefore, they got vaccinated against COVID-19 to minimize the risks of the infection.